Caracterização de argilas para utilização em camadas de impermeabilização em sistemas de cobertura de aterros sanitários no semiárido - Magalhães, Paulo Rossy Forte (2019)
Landfills are works built for the safe containment of solid urban waste. Among its design elements, the waterproofing layer of the final cover stands out, generally built with clay soils, which should minimize, as much as possible, the infiltration of rainwater into the landfill and the escape of gases into the environment. The physical, chemical and mineralogical characteristics of the materials in this layer must be analyzed to assess their potential for use, in addition to analyzes of the performance of the waterproofing layer for local climatic conditions. The present work aims to evaluate the performance of clay soils as a waterproofing material for landfill roofing systems. For that, two samples were selected to perform geotechnical and mineralogical tests. One of the samples was chosen for the construction of an experimental layer with a thickness of 20 cm of compacted clay in an acrylic tube with a diameter of 30 cm. Variations in moisture content at different depths of the layer were measured using electronic sensors in order to monitor the drying process and the formation of cracks. A model for evaluating the volumetric contraction of the material was added to the research. The studied samples presented characteristics compatible with the requirements of the consulted standards. As for the experimental layer, the formation of cracks was limited to the surface. After the evaporation period, a hydraulic load was applied to the surface of the layer, causing the cracks to close and recovering the system's tightness. Although the cracks have not reached the entire depth of the experimental layer, there is a need to verify the performance of the clay layer through an experimental field model, subject to the climatic conditions of the northeastern semiarid.